2019
DOI: 10.1155/2019/6806790
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Anthocyanins and Optimization of Their Extraction from Rabbiteye Blueberry Fruits in Nanjing

Abstract: Blueberries are rich in bioactive anthocyanins, which are associated with health benefits contributing to reducing the risk of diabetes and cardiovascular diseases. The objective of this study was to improve the yield of anthocyanins extracted from rabbiteye blueberry (Vaccinium ashei) fruits cultivated in Nanjing using ultrasound-assisted extraction and to identify the individual anthocyanins present in the extract. The extraction conditions of blueberry anthocyanins were optimized using response surface meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Różańska and Regulska-Ilow found that malvidin was the most content/quantity anthocyanidin found in blueberry, followed by delphinidin, petunidin, peonidin, and cyaniding [16]. In our previous study, malvidin was also confirmed as the largest anthocyanidin found in Brightwell rabbiteye blueberry (Vaccinium ashei) of Nanjing, mostly as malvidin-3-glucoside (Mv-3-glc) and malvidin-3-galactoside (Mv-3-gal) [17]. We tried to investigate the different bioactivities of blueberry anthocyanin extract as well as its major constituents Mv-3-glc and Mv-3-gal and found they could improve endothelial function by protecting against oxidative stress [18,19].…”
Section: Introductionmentioning
confidence: 81%
“…Różańska and Regulska-Ilow found that malvidin was the most content/quantity anthocyanidin found in blueberry, followed by delphinidin, petunidin, peonidin, and cyaniding [16]. In our previous study, malvidin was also confirmed as the largest anthocyanidin found in Brightwell rabbiteye blueberry (Vaccinium ashei) of Nanjing, mostly as malvidin-3-glucoside (Mv-3-glc) and malvidin-3-galactoside (Mv-3-gal) [17]. We tried to investigate the different bioactivities of blueberry anthocyanin extract as well as its major constituents Mv-3-glc and Mv-3-gal and found they could improve endothelial function by protecting against oxidative stress [18,19].…”
Section: Introductionmentioning
confidence: 81%
“…Anthocyanins analysis was carried out according to HPLC methods [ 22 ] with some modifications. The samples were filtered through a 0.22 μm polyvinylidene fluoride membrane before HPLC (Waters 2695, Milford, MA, USA) with a reverse phase C18 column (ZORBAX C18 250 mm × 4.6 mm × 5 μm, Agilent, Santa Clara, CA, USA) and wavelength of 520 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Individual anthocyanins and their derivates in extracts and foulants. Identification based on MS and published data[22].…”
mentioning
confidence: 99%
“…The co‐extraction of anthocyanins, polyphenols, and pectin is limited by the differences in the optimum extraction temperatures required for the effective recovery of each of the products. Anthocyanins are generally extracted at temperatures below 50 °C to avoid degradation 9–11 . However, the optimum temperature range for anthocyanins is not sufficient for recovery of polyphenols and pectin.…”
Section: Introductionmentioning
confidence: 99%